The Semon Lectures and the foundation of modern ENT. Issue 1 (29th November 2021) - Chapple, C; Watkinson, J
Abstract: Background: Sir Felix Semon established the Semon Lecture series in 1913 to advance the specialty of laryngology. The annual lectures continue to the present day (there have been 95 to date). Objective: This review illustrates how instrumental these lectures have been in shaping otolaryngology. Method: The period 1913–1970 preceded subspecialisation, and so forms the background of laryngology (as well as rhinology and otology) as we know it today. This era forms the focus of the article. Results: Changes came about by a standardisation of practices and research, and in the treatment of conditions. The initial period was crucial. Conclusion: Many lectures highlight the specialty's growth. Now, another vital resource, a dedicated website (semonlectures.org), has made this information more accessible to the wider public.